Exploring the impact of emotion on future sustainable development education: Leveraging virtual reality technology / Yi Zhongyao, Mohd Khairulnizam Ramlie and Shafilla Subri - Yi, Zhongyao; Ramlie, Mohd Khairulnizam; Subri, Shafilla (Universiti Teknologi MARA, Perak, 2024)
The 2015 United Nations Millennium Declaration identified 17 sustainable development goals (SDGs) and 169 sub-goals. Sustainability has always been an area of great concern. The main purpose of this study is to explore the role of emotion in promoting the innovation of education for sustainable development in the future through virtual reality technology. The main target group of this study is to promote the United Nations Sustainable Development Goal 13 climate change to people in developed regions. The main medium of communication is virtual reality animation video and game interaction, which is convenient for more users to access through online platforms. Participants can work together online to create sustainable animation and game projects. The 3D animation of virtual reality adopts more realistic modeling, lighting rendering, and material rendering. Issues such as deforestation and ocean acidification can be better visualized. People in developed regions may understand sustainable development but they do not have a deep understanding of the importance of the problem. Therefore, this research is dedicated to making people have a true emotional identity through virtual reality technology, and ultimately transforming people's values, behaviors and lifestyles towards sustainable development.